Analysis of Love, Death, Rebirth and Patriarchy in Two Contemporary Poetess Forough Farrokhzad and Sylvia Plath’s Selected Poems - Narges Raoufzadeh; Sharzad Mohammad Hosein; Shiva Zaheri Birgani (Budapest International Research and Critics University, 2019)
ForoughFarrokhzad and Sylvia Plath’s poems are closely linked to their personal life and their marriage. Their poems are confessional in style. Farrokhzad criticizes Iranian male dominant society in which women are marginalized and haven’t any voice in the society, so seeking their voice and identity in modern literature, especially in modern Persian poetry. Sylvia Plath attempts to resist patriarchy in her society through her poems too. Two poets highlighting and expressing the lack of interest in life and the sole desire to die in most of their poems. Not only poetic imagery and themes like death, frustration and failure are common points that convey pessimistic views in their poems, but also few of their poems convey optimistic elements of life and hope so this paper is going to explain them too. Farrokhzad and Plath, two contemporary female poets, attempted to gain a voice for women in their country. They are considered as the successful feminist voices in their countries and astonishingly share the same themes and issues in their poetry. The present paper aims to highlight characteristics of confessional poetry and elaborate on concepts of love, death, rebirth and patriarchy in ForoughFarrokhzad and Sylvia Plath’s poems.